Contribution of MSME in the Economic Development of India - Kumar Garg, Dr. Vinay; Agarwal, Pragati (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The Micro, Small and Medium Enterprises (MSMEs) sector is a major contributor to the socio- economic development of the country. In India, the sector has gained significant importance due to its contribution to Gross Domestic Product (GDP) of the country and exports. The present paper is based on the objective to study on contribution of MSMEs in Exports and Employment generation in the country and growth and opportunities of this sector. Government of India has been taken numerous initiatives to strengthen this sector and improvement in percentage share in exports and employment of the country. It is concluded that MSMEs significantly contribute in employment, exports and in economic development of India. Keywords – MSME, Export, Employment, Growth, Contribution.